COLOR IN PAINTING (SPECIAL REFERENCE AJANTA): चित्रकला में रंग (विशेष संदर्भ अजन्ता) - Sharma, Seema; Dutt Upadhyay, Priya (International Journal of Research -GRANTHAALAYAH, 2014)
Color has an important place in human life. Each item has a color. It is visible to us only because of the color of the objects in the ground. Objects of the same color appear differently due to less or more light on the ground. The same object will look different in a closed room, in the sun and in different seasons or at different places, due to the amount of light and the color of the atmosphere due to the atmosphere. Human attractiveness to colors has never diminished because color is a medium of attractiveness. That is why, from the tribals to the modern humans, Color is used in development. There is a lot of neglect of shadow light in Indian paintings. Flat colors are usually filled. To show the bulge in some places, use dark colors on the edges (like in the breasts). From the color arrangement of the room to the garden, to the color scheme of flowers and plants in gardens, he has intervened because colors have their own effect which has the power to distract the human mental feelings. The secret energy is hidden in the color that it can provide an eternal mobility. मानव जीवन में रंग का महत्वपूर्ण स्थान है। प्रत्येक वस्तु कोई न कोई रंग लिए है। वस्तुओं के धरातल मे रंग होने के कारण ही वह हमें दिखाई देती है। धरातलों पर प्रकाश की मात्रा कम अथवा अधिक होने से एक ही रंग की वस्तुयें अलग-अलग दिखाई देती हैं। एक ही वस्तु बन्द कमरे में, धूप में तथा विभन्न ऋतुओं में अथवा विभिन्न स्थानों पर प्रकाश की मात्रा तथा वातावरण के कारण रंग व्यवस्था की एक रंगत होते हुये भी भिन्न दिखाई देगी। रंगों के प्रति मानव का आकर्षक कभी नहीं घटा है क्योंकि रंग आकर्षक का एक माध्यम है। इसलिये तो आदिवासियों से लेकर आधुनिक मानव तक ने सौन्दर्य के विकास में रंग का सहारा लिया है। भारतीय चित्रों में छाया प्रकाश की बहुत उपेक्षा रहती है। प्रायः सपाट रंग ही भरे जाते हैं। कहीं-कहीं उभार दिखाने के लिये किनारों पर गहरे रंग का (जैसे स्तनों में) प्रयोग कर लेते है। कमरे को रंग व्यवस्था से लकर बाग, बगीचों में फूल - पौधो की रंग योजना तक में उसने अपना हस्तक्षेप किया है क्योंकि रंगों का अपना एक प्रभाव होता है जो मानव की मानसिक भावनाओं को विचलित करने की शक्ति रखता है। रंग में वह गुप्त ऊर्जा छिपी होती है कि वह एक अनन्त गतिशीलता प्रदान कर सकती है।